Características agronômicas, adaptabilidade e estabilidade fenotípica da produtividade de genótipos de quinoa no Brasil - Santos, Bruno Capelani dos (2021)
The quinoa crop has been gaining emphasis in Brazil due to its growing consumption and nutritional value, however, there are few studies aimed at this crop, especially when it comes to adaptability and stability considering the grain yield. The objective of this work was to evaluate the agronomic characteristics and identify, through different methods, the genotypes with better stability and productive adaptability in different environments. The genotypes were evaluated in a complete block design with randomized treatments, evaluated in seven environments. The variables analyzed were days until flowering, inflorescence height, flowering height, height at harvest and grain yield. The adaptability and stability assessment was carried out following the methodologies: Yates and Cochran; Eberhart and Russell; Cruz, Torres and Vencovsky and the Integrated method aimed at adaptability and stability. Genotypes Q2014, Q1304, Q1307 and Q1320 can be considered as possible candidates to constitute a new variety of quinoa, showing adaptability and stability to the environmental conditions in which they were evaluated. The Q2014 genotype showed agronomic potential, adaptability and phenotypic stability in general, being selected as a possible cultivar for use in the western region of Paraná.